Sistem Kendali Dan Monitoring Tingkat Kekeruhan Air Pada Air PDAM Menggunakan Arduino Uno - Faisal Ibramsah Pademui; Khozainuz Zuhri; Destoprani Brajannoto (Jurnal Teknologi dan Informatika (JEDA), 2022)
Based on the survey that has been carried out, the PDAM operator detects turbidity in the water treatment plant using the conventional method (visual) and records the value of changes in turbidity that occur manually. This device is controlled by an Arduino uno microcontroller IC as a command process to be executed and a turbidity sensor that will detect turbidity in water and smartphones as monitoring media and turbidity sensor data application media. After various tests and analyzes have been carried out on the control design and monitoring of PDAM water turbidity, the measurement of this system uses the Turbidity sensor module so that it can facilitate the measurement of PDAM water turbidity and water control so that the water is not cloudy with a tool control system carried out by internet communication using the IOT method. (Internet of Things) and also the water pump motor uses a 220v AC type poma motor and uses a water filter to purify the water.